Docetaxel-Loaded Poly(3HB-co-4HB) Biodegradable Nanoparticles: Impact of Copolymer Composition - Faisalina, A.F. (Nanomaterials (Basel), 2020)
Polyhydroxyalkanoate (PHA) copolymers show a relatively higher in vivo degradation rate compared to other PHAs, thus, they receive a great deal of attention for a wide range of medical applications. Nanoparticles (NPs) loaded with poorly water-soluble anticancer drug docetaxel (DCX) were produced using poly(3-hydroxybutyrate-co-4-hydroxybutyrate), P(3HB-co-4HB), copolymers biosynthesised from Cupriavidus malaysiensis USMAA1020 isolated from the Malaysian environment. Three copolymers with different molar proportions of 4-hydroxybutirate (4HB) were used: 16% (PHB16), 30% (PHB30) and 70% (PHB70) 4HB-containing P(3HB-co-4HB). Blank and DCX-loaded nanoparticles were then characterized for their size and size distribution, surface charge, encapsulation efficiency and drug release. Preformulation studies showed that an optimised formulation could be achieved through the emulsification/solvent evaporation method using PHB70 with the addition of 1.0% PVA, as stabilizer and 0.03% VitE-TPGS, as surfactant. DCX-loaded PHB70 nanoparticles (DCX-PHB70) gave the desired particle size distribution in terms of average particle size around 150 nm and narrow particle size distribution (polydispersity index (PDI) below 0.100). The encapsulation efficiency result showed that at 30% w/w drug-to-polymer ratio: DCX- PHB16 NPs were able to encapsulate up to 42% of DCX; DCX-PHB30 NPs encapsulated up to 46% of DCX and DCX-PHB70 NPs encapsulated up to 50% of DCX within the nanoparticle system. Approximately 60% of DCX was released from the DCX-PHB70 NPs within 7 days for 5%, 10% and 20% of drug-to-polymer ratio while for the 30% and 40% drug-to-polymer ratios, an almost complete drug release (98%) after 7 days of incubation was observed.